A Hard Rain's a-Gonna Fall? New Insights on Water Security and Fragility in the Sahel - Khan, Amjad Muhammad (World Bank, Washington, DC, 2021)
Do Sahelian countries face specific risks of water-related conflict Sahelian countries face growing fragility and climate challenges—especially those belonging to the Group of Five Sahel States (known as the G5 Sahel)—Burkina Faso, Chad, Mali, Mauritania, and Niger. This study examines how their relation to water availability and irrigation infrastructure factors in. It documents that the G5 Sahel countries, given their high baseline water scarcity and state fragility, face a higher risk of conflict over water resources compared to the rest of Africa. This is demonstrated through empirical analyses using geospatial data and exploiting (i) climate-induced variation in water availability, and (ii) an event study analysis of conflict trends, which sharply increased post-2010 in the region following the Arab Spring and the rise of the Boko Haram. Irrigated areas are found to be important for buffering against weather shocks but are also more prone to targeting during conflict events compared to non-irrigated regions. The evidence suggests that this reflects increased competition for scarce (fertile) resources between state and rebel groups on this climate frontier with a well-documented history of agropastoral conflict. Other regions of Africa are not found to experience similar conflict related to water resources. These findings are especially pertinent for informing projects and policy interventions in fragile countries as post-COVID-19 recovery and climate action plans are rolled out.